Enriched environment impacts trimethylthiazoline‐induced anxiety‐related behavior and immediate early gene expression: critical role of Crhr1. (20th May 2014) - Sotnikov, S. V.; Chekmareva, N. Y.; Schmid, B.; Harbich, D.; Malik, V.; Bauer, S.; Kuehne, C.; Markt, P. O.; Deussing, J. M.; Schmidt, M. V.; Landgraf, R.
Abstract It has been shown previously (Sotnikov et al., 2011) that mice selectively inbred for high anxiety‐related behavior (HAB) vs. low anxiety‐related behavior in the elevated plus maze differentially respond to trimethylthiazoline (TMT), a synthetic fox fecal odor. However, less is known about whether environmental factors can rescue these extreme phenotypes. Here, we found that an enriched environment (EE) provided during early adolescence induced anxiolytic effects in HAB (HAB‐EE) mice, rescuing their strong avoidance behavior induced by TMT. In a series of experiments, the contribution of maternal, juvenile and adolescent behavior to the anxiolytic effects elicited by EE was investigated. At the molecular level, using c‐fos expression mapping, we found that the activity of the medial and basolateral amygdala was significantly reduced in HAB‐EE mice after TMT exposure. We further analysed the expression of Crhr1, as its amount in the amygdala has been reported to be important for the regulation of anxiety‐related behavior after EE. Indeed, in situ hybridisation indicated significantly decreased Crhr1 expression in the basolateral and central amygdala of HAB‐EE mice. To further test the involvement of Crhr1 in TMT‐induced avoidance, we exposed conditional glutamatergic‐specific Crhr1‐knockout mice to the odor. The behavioral response of Crhr1‐knockout mice mimicked that of HAB‐EE mice, and c‐fos expression in the amygdala after TMT exposure was significantly lower compared with controls, thereby further supporting a critical involvement of Crhr1 in environmentally‐induced anxiolysis. Altogether, our results indicate that EE can rescue strong avoidance of TMT by HAB mice with Crhr1 expression in the amygdala being critically involved.